ANALISIS TERHADAP PERILAKU KONSUMEN PRODUK FASHION MUSLIM - Anju Ayunda; Lu’liyatul Mutmainah; Nurul Huda (Journal of Economics and Business Aseanomics (JEBA), 2019)
This study aims to determine how the level of consumers who are represented by respondents as the object under study to purchase Muslim Fashion product and how to choose in determining shopping place/media. Although consumers of Muslim Fashion product have understood Islamic sharia ethics, yet innovative breakthroughs continue to create exciting amenities and offers and eventually may influence to Muslims consumption behaviour.